Integration of GWAS, QTLs and keratinocyte functional assays reveals molecular mechanisms of atopic dermatitis - Meritxell Oliva; Mrinal K. Sarkar; Michael E. March; Amir Hossein Saeidian; Frank D. Mentch; Chen-Lin Hsieh; Fanying Tang; Ranjitha Uppala; Matthew T. Patrick; Qinmengge Li; Rachael Bogle; J. Michelle Kahlenberg; et al. (Nature Communications)
Abstract Atopic dermatitis is a highly heritable and common inflammatory skin condition affecting children and adults worldwide. Multi-ancestry approaches to atopic dermatitis genetic association studies are poised to boost power to detect genetic signal and identify loci contributing to atopic dermatitis risk. Here, we present a multi-ancestry GWAS meta-analysis of twelve atopic dermatitis cohorts from five ancestral populations totaling 56,146 cases and 602,280 controls. We report 101 genomic loci associated with atopic dermatitis, including 16 loci that have not been previously associated with atopic dermatitis or eczema. Fine-mapping, QTL colocalization, and cell-type enrichment analyses identified genes and cell types implicated in atopic dermatitis pathophysiology. Functional analyses in keratinocytes provide evidence for genes that could play a role in atopic dermatitis through epidermal barrier function. Our study provides insights into the etiology of atopic dermatitis by harnessing multiple genetic and functional approaches to unveil the mechanisms by which atopic dermatitis-associated variants impact genes and cell types.